2003
DOI: 10.1021/ma0349682
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2-Mediated Intercalation of PEO in Clay

Abstract: Introduction. Polymer/clay nanocomposites prepared by a variety of methods that embed these inorganic nanolayers to a polymer host have been actively studied in recent years as these materials exhibit dramatic, concurrent improvements in many properties. 1 Typical preparation methods include in-situ polymerization, solution intercalation, and melt intercalation, among which solution intercalation has been known for over a century and has proved to be one of the most successful methods of incorporating delamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
(44 reference statements)
4
31
0
Order By: Relevance
“…Therefore, it was concluded that the ScCO 2 preparation yielded more homogenous samples as no non-intercalated PEO remained in the composites prepared using ScCO 2 . The findings of the DSC analysis is in agreement with those reported by Zhao and Samulski [6] who found that, compared with composites prepared by solution methods, composites prepared via ScCO 2 processing had lower T m and smaller ΔH m .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it was concluded that the ScCO 2 preparation yielded more homogenous samples as no non-intercalated PEO remained in the composites prepared using ScCO 2 . The findings of the DSC analysis is in agreement with those reported by Zhao and Samulski [6] who found that, compared with composites prepared by solution methods, composites prepared via ScCO 2 processing had lower T m and smaller ΔH m .…”
supporting
confidence: 91%
“…Zhao and Samulski reported the preparation of polymer/nanoclay composites with PEO of molecular weight 10,000 using ScCO 2 processing [6]. Their study compared two methods of sample preparation in which the PEO was intercalated into montmorillonite clay via either a small scale (2.5 ml chamber) ScCO 2 process or solution modification using water or alcohol as solvent.…”
mentioning
confidence: 99%
“…20 Zhao et al 21 presented unambiguous evidence for sc-CO 2 mediated intercalation of PEO into Na z -MMT compared with polymer intercalation in solution, in which an entropy driven process is dominant. This mechanism is probably similar to that in polymer melts.…”
Section: Nobel Compounding Processmentioning
confidence: 99%
“…54 kJ mol 21 / 32 . 09 kJ mol 21 ), which is the energetic interaction parameter between polymer clay and polymer polymer. It is also reported the value of the free volume reduction for the polystyrene based nanocomposite system.…”
Section: Pressure Volume Temperature (Pvt) Behaviourmentioning
confidence: 99%
“…All PBSCNs studied here follow this relation except PBSCN4 (MMT5 3 . 6 wt-%), in which w filler &(aspect ratio) 21 . For this reason in PBSCN4 rotation of dispersed intercalated with flocculated stacked silicate layers is completely hindered and only translational motion is available, and hence show very high modulus.…”
Section: Flocculation Control and Modulus Enhancementmentioning
confidence: 99%